Design of Hardware Setup Based on IEC 61850 Communication Protocol for Detection & Blocking of Harmonics in Power Transformer - Abdul Azeem; Majid Jamil; Shamimul Qamar; Hasmat Malik; Rayees Ahmad Thokar (Energies, 2021)
In this paper, the authors have developed a hardware model for blocking even and odd harmonics of a power transformer. In the proposed hardware model, intelligent differential & over-current relays are used for the blocking of harmonics of a power transformer. The harmonic restraint function on the differential relay (7UT61) prevents the relay from tripping during transformer magnetizing inrush current. However, the over-current relays which are used for back up protection does not have a harmonic restraint element, and over-current relay trips due to magnetizing inrush current, causes unwanted interruptions and power failures. The establishment of harmonic blocking scheme for over-current protection in power transformers is an important finding of this research study. IEC61850 standard-Based GOOSE (Generic Object Oriented Substation Event) applications used in power transformer protection for fast detecting and clearing of faults is an interested study presented in the proposed work.